Antiquarian knights in Mediterranean island landscapes: the Hospitaller Order of St John and crusading among the ruins of classical antiquity, from medieval Rhodes to early modern Malta. Issue 3 (27th May 2021) - Brown, Amelia Robertson
ABSTRACT: From 1306 to 1798, the Hospitaller Order of the knights of St John was headquartered on the Mediterranean islands of Rhodes and Malta. These 'crusaders' encountered island landscapes, ancient texts and monumental ruins of Graeco-Roman antiquity there first-hand. Their attitude to ancient sculpture and inscriptions changed over time, however, as did their scholarship of classical Greek, Roman or Byzantine texts and antiquities. Their antiquarianism shifted as some retreated from battlefields or hospitals, connecting with the literary, material and Christianised legacy of ancient Greece and Rome around them. Ruins like the Mausoleum of Halicarnassus were rebuilt into fortifications c .1500, but by 1647, Commendatore G. F. Abela was collecting, and writing about, his own 'modern' museum of classical antiquities on Malta. Antiquarian activities of the Hospitaller Knights thus chart the growth of both neoclassicism and the academic study of the Mediterranean islands in antiquity, forming a key legacy of the Order.